Synthesis and Preliminary Antibacterial Effects of New 1, 3, 4-Oxadiazoles - Zeid Hassan Abood (Journal of Global Pharma Technology, 2020)
4-aminobenzoyl hydrazide [I] was reacted with carbon disulfide in the existence of potassium hydroxide in ethyl alcohol to give 5-(4-aminophenyl)-2-thiol-1,3,4-oxadiazole [II]. The initiator aldehyde [III] was prepared via coupling reaction of 2-hydroxybenzaldehyde with the corresponding diazonium salt of compound [II]. Aldehyde [III] was condensed with some anilines including (3-bromoaniline, 4-aminophenol, 3-aminophenol, 2-aminophenol, 4-methoxyaniline, 2, 4-dimethylaniline and 4-acetamidoaniline) utilizing microwave irradiation technique in ethyl alcohol to yield seven imines [IV] a-g. Treatment of imines [IV]a-g with phthalic anhydride in microwave oven gave seven 1,3-benzoxazepine-4,7-diones derivatives of 1,3,4-oxadiazole [V]a-g. The antibacterial activities for the desired compounds were investigated on bacteria, Staphylococcus aurous and Escherichia coli. The results showed that the synthesized 1, 3, 4-oxadiazoles (compounds [V]a, [V]b, [V]c, [V]d and [V]e expressed better activity to gentamycin athwart positive bacteria. On the other hand, the 1,3-oxazepine-4,7-diones [V]a, [V]b, [V]c, [V]d, [V]f and [V]g exhibited greater effect against negative bacteria in comparison with that of the control drug (Gentamycin).Keywords: 1, 3, 4-Oxadiazoles, Benzoxazepines, Imines, Cycloaddition, Antibacterial action.